التكوين أثناء الخدمة وعلاقته بالأداء الوظيفي لأساتذة التعليم الإبتدائي - حميدة، مسعودة, رقيق، بشيرة (جامعة الوادي university of Eloued, 2020)
The study titled in-service training and its relationship to the job performance of elementary education teachers aimed to highlight the role of training, its characteristics and objectives, as well as to reveal the extent of the contribution of in-service training to the development of the job performance of primary education teachers, And the extent of its effectiveness in developing and improving their level in the performance of their profession in terms of planning study and implementation and the process of evaluating the educational process through the following question: Is there a relationship between training during service and the development of the job performance of primary school teachers? The following hypotheses were developed There is a relationship between training during the service and career development of elementary school teachers in terms of planning lessons . There is a relationship between training during the service and the development of the job performance of elementary school teachers with regard to implementation. There is a relationship between training during the service and career development of elementary school teachers with regard to evaluation. We chose the descriptive approach , The sample was intended toinclude 64 male and female teachers from the primary schools of HassiKhalifa municipality in the wilaya of El-Wadi. We have designed a questionnaire form that includes the three axes: planning , Implementation, Calendar. But unfortunately, we were unable to distribute the form to the sample members, due to the pandemic of the Coronavirus that prevented us from collecting and analyzing information
دراسة ميدانية بمدارس المقاطعة الأولى بحاسي خليفة
مذكرة ماستر في علم الإجتماع تخصص علم إجتماع التربية
Keywords: تكوين المعلمين، الأداء الوظيفي; Formation des enseignants, performance au travail; Teacher training, job performance